2016
DOI: 10.5301/jva.5000554
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Access through a Persistent left Superior Vena Cava: A Case Series

Abstract: A persistent left superior vena cava (PLSVC) is a rare, under-recognized congenital anomaly. The PLSVC is incidentally discovered during central venous access procedures when access is obtained from the left internal jugular vein. The vast majority of PLSVCs drain into the right atrium; however, it is critical to recognize a PLSVC that drains into the left atrium as it can predispose to systemic dispersion of emboli through bypassing the lungs. Additionally, PLSVC catheterization has also been previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The persistent left SVC is a common congenital variation with no clinical significance, which is seen in 0.3% of healthy patients and 4.3% of patients with congenital heart disease 6,7 . The most common subtype of persistent left SVC results in the presence of both left and right SVCs 8,9 . More rarely, abnormalities of the embryological development lead to an absent right SVC with persistent left SVC, as previously described in both pediatric and adult patients [10][11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The persistent left SVC is a common congenital variation with no clinical significance, which is seen in 0.3% of healthy patients and 4.3% of patients with congenital heart disease 6,7 . The most common subtype of persistent left SVC results in the presence of both left and right SVCs 8,9 . More rarely, abnormalities of the embryological development lead to an absent right SVC with persistent left SVC, as previously described in both pediatric and adult patients [10][11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…PLSVC is the most common thoracic venous anomaly (Sarodia and Stoller, 2000). A predominant associated concern for the clinician is mechanical vascular damage by forceful manipulation, thrombosis, or cardiac arrest secondary to coronary sinus irritation (Zhou et al, 2016). Because PLSVC is largely asymptomatic, it is usually diagnosed incidentally.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Vascular Access 19 (4) echocardiography and angiographic investigations prior to catheterization. 4 Kute VB et al 5 have also successfully demonstrated safe use of HD catheter into the PLSVC for 2 months.…”
mentioning
confidence: 99%